Shrines in Africa History, Politics, and Society - Dawson, Allan C. (Africa: Missing Voices, 2009)
In the African context, shrines are cultural signposts that help one understand and read the ethnic, territorial, and social lay of the land. The contributions gathered here by Allan Charles Dawson demonstrate how African shrines help to define ethnic boundaries, shape group identity, and symbolically articulate a society's connection with the land it occupies. Shrines are physical manifestations of a group's claim to a particular piece of land and are thus markers of identity - they represent, both figuratively and literally, a community's 'roots' in the land it works and lives on. The shrine is representative of a connection with the land at the cosmological and supernatural level and, in terms of a community's or ethnic group's claim to cultivable territory, serves as a reminder to outsiders of ownership. This volume explores how African shrines, in all their variable and diverse forms, are more than just spiritual vessels or points of worship - they are powerful symbols of ethnic solidarity, group cohesion, and knowledge about the landscape. Moreover, in ways subtle and nuanced, shrines represent ideas about legitimacy and authenticity in the context of the post-colonial African state.